MEMUPUK KEBERAKSARAAN: BERINOVASI DALAM PERSPEKTIF BELAJAR SEPANJANG HAYAT - Mustakim Mustakim; Eko Sulistiono; Iip Saripah; Fahmi Dinni (Comm-Edu (Community Education Journal), 2021)
Many studies have suggested the relationship between innovation and lifelong learning that are interrelated. However, it is still difficult to find research that takes the viewpoint of innovation as an implication of a lifelong learning process which cultivates literacy. By collecting conceptual literatures on innovation and lifelong learning, this article aims to provide a perspective view of the concept of lifelong learning in innovation. This article also contributes to encourage adults to have the mindset to always learn without being limited by space and time in creating innovation so as to avoid being illiterate again. The findings of this article suggest the idea that innovation can create learning processes. Even in the learning process, it can have implications for innovation. In the future research requires a significant amount of time to examine various perspectives and conceptual issues related to innovation seen in the perspective of lifelong learning.